UJI TOKSISITAS AKUT (LC50-96 Jam dan LT50-96 Jam) INSEKTISDA KLORPIRIFOS TERHADAP IKAN NILA (Oreochromis niloticus) - Fransiskus Bernas Deviero Siregar; Ipanna Enggar Susetya (AQUACOASTMARINE, 2018)
Tilapia (Oreochromis niloticus) included to the family of Cichlidae. Tilapia (Oreochromis niloticus) has economic value for humans, Tilapia could found in freshwater. The poor water quality could impact to the growth of the fish. One of the causes of the decrease water quality in aquatic environment were the waste from activities around the water, such as agricultural’s waste. The used of insecticide of chlorpyrifos could causes the accumulation of chlorpyrifos in the soil and then carried by water into the water body that would pollute the water body. This research aimed to determine the value of LC50-96 hours & LT50-96 hours of the used of chlorpyrifos on the mortality of tilapia (Oreochromis niloticus) and the impact of toxicity in chlorpyrifos toward tilapia (Oreochromis niloticus). This research was conducted between March 2018 and April 2018 at the Laboratory of Aquaculture and Aquatic Biology. Test results showed that the value of LC50-96 Hours were 0.29 ppm and LT50-96 Hours were 12 hours. The highest survival result was obtained at 0.0063 ppm with score 93.33% and the lowest result was at 9.9096 ppm with score 3.33%. The result of water quality still in good condition.Keywords: Tilapia (Oreochromis niloticus), Klorpirifos Insecticide, LC50, LT50.